2018
DOI: 10.1186/s12916-018-1193-5
|View full text |Cite
|
Sign up to set email alerts
|

Selective serotonin reuptake inhibitor use during early pregnancy and congenital malformations: a systematic review and meta-analysis of cohort studies of more than 9 million births

Abstract: BackgroundIn 2005, the FDA cautioned that exposure to paroxetine, a selective serotonin reuptake inhibitor (SSRI), during the first trimester of pregnancy may increase the risk of cardiac malformations. Since then, the association between maternal use of SSRIs during pregnancy and congenital malformations in infants has been the subject of much discussion and controversy. The aim of this study is to systematically review the associations between SSRIs use during early pregnancy and the risk of congenital malfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 82 publications
(178 reference statements)
4
77
0
Order By: Relevance
“…With respect to SSRIs, database studies that have not controlled for maternal depression have reported an increased risk of cardiac septal defects in neonates exposed to SSRIs in utero (Gao et al, 2018;Kallen and Otterblad, 2007;Shen et al, 2017), but for the majority of SSRIs this effect is no longer statistically significant when maternal depression (Gao et al, 2018;Huybrechts et al, 2014) and lifestyle risk factors are controlled for (Huybrechts et al, 2014); data relating to sertraline are insufficient to allow an effect to be excluded (Gao et al, 2018).…”
Section: Selective Serotonin Reuptake Inhibitor (Ssri) Antidepressantmentioning
confidence: 99%
“…With respect to SSRIs, database studies that have not controlled for maternal depression have reported an increased risk of cardiac septal defects in neonates exposed to SSRIs in utero (Gao et al, 2018;Kallen and Otterblad, 2007;Shen et al, 2017), but for the majority of SSRIs this effect is no longer statistically significant when maternal depression (Gao et al, 2018;Huybrechts et al, 2014) and lifestyle risk factors are controlled for (Huybrechts et al, 2014); data relating to sertraline are insufficient to allow an effect to be excluded (Gao et al, 2018).…”
Section: Selective Serotonin Reuptake Inhibitor (Ssri) Antidepressantmentioning
confidence: 99%
“…Selective serotonin reuptake inhibitors (SSRIs) are the most widely prescribed secondgeneration antidepressant drugs. These drugs have also been implicated in a small increased risk of offspring CHD (Bérard et al 2017;Gao et al 2018). However, this is somewhat controversial, as this association may disappear when corrected for confounding factors (Huybrechts et al 2014).…”
Section: Antidepressantsmentioning
confidence: 99%
“…This may have occurred because in 2005, the FDA cautioned that exposure to paroxetine during the first trimester of pregnancy may increase the risk of cardiac malformations [38]; this information was not divulged in Japan. Recently, a meta-analysis study reported a generally small risk of congenital malformations of selective serotonin reuptake inhibitors in pregnancy [39]. Although the OR of Cong in class 6, which included antiepileptic drugs with multiple medications, was higher than 1 in both datasets, it was not higher than that of class 1.…”
Section: Discussionmentioning
confidence: 89%